ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸Ð¸ ÐºÐ»ÐµÑ‚Ð¾Ðº Ð½Ð°Ð´Ð¿Ð¾Ñ‡ÐµÑ‡Ð½Ð¸ÐºÐ¾Ð² Ð½Ð¾Ð²Ð¾Ñ€Ð¾Ð¶Ð´ÐµÐ½Ð½Ñ‹Ñ… Ð¼Ñ‹ÑˆÐµÐ¹. II. Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð°Ñ†Ð¸Ð¹ ÑÑ‹Ð²Ð¾Ñ€Ð¾Ñ‚ÐºÐ¸ Ð² ÑÐ¾ÑÑ‚Ð°Ð²Ðµ ÐºÑ€Ð¸Ð¾Ð·Ð°Ñ‰Ð¸Ñ‚Ð½Ð¾Ð¹ ÑÑ€ÐµÐ´Ñ‹ - Tamarina, Irina V.; Bozhok, Galina A.; Gurina, Tatyana M.; Gubina, Nina F.; Bondarenko, Tatyana P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
The effect of fetal bovine serum (FBS) and dimethylsulfoxide (DMSO) concentrations within cryoprotective medium on the viability indices by exclusion of trypan blue, survival and hormonal activity of adrenal cells of newborn mice after freeze-thawing has been studied. Application of 10 and 25% serum enabled to increase a number of viable adrenal cells of newborn rats if compared with serum-free media. The highest indices of viability (from 71.4 upto 76.0%) and survival (99.0%) were observed after freeze-thawing of adrenal cells in the media, containing 10, 15, 20% DMSO and 25% FBS. However, hormonal and proliferative activities were reduced if compared with the control culture.